Evaluation of granular sludge for secondary treatment of saline municipal sewage. (1st July 2015) - van den Akker, Ben; Reid, Katherine; Middlemiss, Kyra; Krampe, Joerg
Abstract: This study examined the impact of chemical oxygen demand (COD) loading and dissolved oxygen (DO) concentration on the stability and performance of granular sludge treating high saline municipal sewage. Under high DO concentrations of 4.0–7.0 mg/L, and COD loading rates of 0.98 and 1.55 kg/m 3 /d, rapid settling granules were established within four weeks of start-up. Under the highest COD load, a reduction in DO lead to the rapid deterioration of the sludge volume index (SVI) and washout of granules due to prolific growth of the filament Thiothrix Type 021N. Conversely, when operated under a lower COD load, a reduction in DO concentration had no adverse impact on the stability of SVI and granules. A decrease in DO also improved nitrogen removal performance, where simultaneous removal of ammonium (98%), total nitrogen (86%) and BOD5 (98%) were achieved when median DO concentrations were between 1.0 and 1.5 mg/L. Phosphate removal was lower than expected, however the level of biological phosphate removal activity observed appeared sufficient to maintain granule stability, even under low DO concentrations. Nitrous oxide emissions were also characterised, which ranged between 2.3 and 6.8% of the total nitrogen load. Our results confirmed that granular sludge is a viable option for the treatment of saline sewage. Highlights: The application of granular sludge to treat high saline sewage was investigated. Granular sludge was readily established under high saline conditions. COD loading and dissolved oxygen (DO) influenced granule stability and performance. Granular sludge was maintained at low DO despite poor biological phosphate removal.